2023
DOI: 10.3390/inorganics11030121
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxide Materials: A Review on Their Preparation, Characterization, and Applications

Abstract: Layered double hydroxides (LDHs), a type of synthetic clay with assorted potential applications, are deliberated upon in view of their specific properties, such as adsorbent-specific behavior, biocompatibility, fire-retardant capacity, and catalytic and anion exchange properties, among others. LDHs are materials with two-dimensional morphology, high porosity, and exceptionally tunable and exchangeable anionic particles with sensible interlayer spaces. The remarkable feature of LDHs is their flexibility in main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 155 publications
0
34
0
Order By: Relevance
“…[82][83][84][85][86] In general, sonochemistry has significant advantages for the preparation of amorphous substances, the transformation of nanomaterials into mesoporous materials, the deposition of nanoparticles on the surface of ceramic and polymer materials, and the formation of protein-like micro-and nanospheres. [87] For example, ultrasonic treatment of (Ni(NO 3 ) 2 + urea) solution at a frequency of 20 kHz and high power gives highly defective, nano-sized α-Ni(OH) 2 fibers up to 200 nm in length and up to 15 nm in diameter. [83] Application (20 kHz) of low-power kHz ultrasound for the treatment of Ni(NO 3 ) 2 and NH 4 OH solutions leads to the formation of nitrate-intercalated α-Ni(OH) 2 nanoparticles (d � 5 nm).…”
Section: Sonochemical Synthesis (Synthesis Using Ultrasound)mentioning
confidence: 99%
“…[82][83][84][85][86] In general, sonochemistry has significant advantages for the preparation of amorphous substances, the transformation of nanomaterials into mesoporous materials, the deposition of nanoparticles on the surface of ceramic and polymer materials, and the formation of protein-like micro-and nanospheres. [87] For example, ultrasonic treatment of (Ni(NO 3 ) 2 + urea) solution at a frequency of 20 kHz and high power gives highly defective, nano-sized α-Ni(OH) 2 fibers up to 200 nm in length and up to 15 nm in diameter. [83] Application (20 kHz) of low-power kHz ultrasound for the treatment of Ni(NO 3 ) 2 and NH 4 OH solutions leads to the formation of nitrate-intercalated α-Ni(OH) 2 nanoparticles (d � 5 nm).…”
Section: Sonochemical Synthesis (Synthesis Using Ultrasound)mentioning
confidence: 99%
“…35 The main drawbacks in co-precipitation and mechanosynthesis generally include more than four synthesis parameters to control. 2,4,[9][10][11][12][13][14][15][16][17] Synthesis times for co-precipitation vary between a few minutes to more than 8 h, depending on the LDH composition, the nature of intercalation compounds and above all, the crystallization degree expected. The synthesis time for mechanosynthesis is longer, typically more than 12 hours, although studies have reported milling times of less than 1 hour.…”
Section: Perspective Materials Advancesmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Notably, LDHs display a 2D structure, allowing them to be insertion systems for active molecules, pollutants, and so forth, promising numerous smart host-guest materials. For each of these fields, considerable progress has been made recently as highlighted by Kameliya et al 10 with eco-friendly LDH synthesized today for application as catalysts, and in photoelectrocatalysis with amazing results 11 with a strong proof of concept for water decontamination, 12,13 and the sensor-biosensor perspectives are also stemming from these long years of research. Another field where LDHs can be the original material for good solutions is in corrosion protection.…”
Section: Introductionmentioning
confidence: 99%
“…The biomedical and industrial application of natural antioxidants is hindered by their sensitivity to the environmental conditions (e.g., pH, temperature, or electrolytes) and/or limited water solubility, nevertheless, heterogenization using suitable support materials may overcome this drawback. Layered double hydroxides (LDHs) are anionic clays and widely applied as host materials, because of their advantageous properties such as tunable structure, biocompatibility, cost-effectiveness, and relatively easy preparation techniques. LDH structure can be derived from brucite (Mg­(OH) 2 ) by isomorphic substitution of the divalent metal ions with trivalent ones. The most generic formula of an LDH is [M 2+ x M 3+ 1– x (OH) 2 ] [A m0 – x / m · n H 2 O], where M 2+ and M 3+ are the di- and trivalent metal cations, respectively, while A m – is the interlayer charge compensating anion. , The intercalation of biomolecules among LDH layers may reduce the sensitivity of the antioxidants, while the ROS scavenging activity may remain unchanged.…”
Section: Introductionmentioning
confidence: 99%